Pengaruh Digital Marketing Berbasis Marketplace terhadap Peningkatan Penjualan Ledre Super UMKM Perempuan di Bojonegoro - Eka Retno Palupi; Raya Sulistyowati (Ekonomis: Journal of Economics and Business, 2022)
This study aims to identify the effect of marketplace-based digital marketing on increasing sales. Digital marketing with indicators Website, Search Engine, E-Mail Marketing, Cost, Incentive Program. Increased sales with indicators of Price, Product Quality, Promotion, Competitiveness, Consumer Satisfaction. The population in this study was taken from the employees of Ledre Super SMEs in the Padangan-bojonegoro area. This type of research is descriptive quantitative using non-probability sampling technique by taking 220 samples. The population in this study were super ledre employees totaling 69 respondents. The data analysis technique used simple linear analysis. the results of this study indicate that the digital marketing variable partially has a significant effect on increasing sales.